Fading Light, Fierce Winds: JWST Snapshot of a Sub-Eddington Quasar at Cosmic Dawn - Jianwei Lyu; George H. Rieke; Meredith Stone; Jane Morrison; Stacey Alberts; Xiangyu Jin; Yongda Zhu; Weizhe Liu; Jinyi Yang (The Astrophysical Journal Letters)
The majority of most luminous quasars during the epoch of reionization accrete near or above the Eddington limit, marking the vigorous growth of primitive supermassive black holes (SMBHs). However, their subsequent evolution and environmental impact remain poorly characterized. We present JWST/NIRSpec prism integral field unit observations of HSC J2239+0207, a low-luminosity quasar at z ∼ 6.25 likely in a late stage of mass assembly with an overmassive SMBH relative to its host galaxy. Using H β and H α broad emission lines, we estimate an SMBH mass M _BH ∼ 3 × 10 ^8 M _⊙ and confirm its sub-Eddington accretion at λ _Edd ∼ 0.4. Strong Fe ii emission and a proximity zone of typical size suggest a metal-rich, highly evolved system. In the far-UV, this quasar presents strong broad absorption line features, indicative of high-velocity winds ( ν ∼ 10 ^4 km s ^−1 ). Meanwhile, minimal dust reddening is inferred from the quasar continuum and broad-line Balmer decrement, suggesting little dust along the polar direction. Most interestingly, we identify a gas companion ∼5 kpc from the quasar with a high [O iii ]/H β ratio (≳10), likely representing outflowing gas blown away by active galactic nucleus (AGN) feedback. These results highlight HSC J2239+0207 as a likely fading quasar in transition, providing rare insights into SMBH evolution, AGN feedback, and AGN–galaxy interactions in the early Universe.